(untitled) (Physical Education, Health and Social Sciences, 2025)
This paper argues that Faiqa Mansab’s This House of Clay and Water (2017) operates fundamentally as a text of the postcolonial gothic, transcending its established reputation as a socio-realist critique of gender and class in Pakistan. By utilizing Sigmund Freud’s concept of the Unheimlich, this research analyzes how the domestic and spiritual spaces in the novel specifically the elite household and the daata darbar shrine are rendered frighteningly unfamiliar through the return of repressed trauma. The study posits that Lahore acts as a gothic site where the boundaries between the living and the socially dead (the hijra, the grieving mother, the disgraced wife) dissolve. Through a close textual analysis of the protagonists Nida, Sasha, and Bhanggi- the paper demonstrates how their bodies serve as sites of "gothic memory," bearing the scars of historical and personal violence that refuse to remain buried. Nida’s home becomes a tomb for her dead daughter, transforming domesticity into a source of horror, while the shrine serves as a paradoxical "unhomely sanctuary" a space of comfort that is simultaneously marked by violence and abjection. By situating Mansab’s work within the postcolonial gothic tradition, this paper reveals how the novel uses the aesthetics of haunting to critique the stifling patriarchal structures of contemporary urban Pakistan, ultimately suggesting that for the marginalized, there is no "home," only a series of hauntings.